EDUCATION OF STUDENT CHARACTER VALUE ON RELIGIOUS AND CULTURAL DIVERSITY STUDENTS' MULTICULTURAL CLASS PROGRAM DARMA BAKTI KARYA PANGANDARAN FOUNDATION - Nunung Nursyamsiah; Hikmah Maulani; Sofyan Sauri; Mad 'Ali; Rinaldi Supriadi (Universitas Negeri Medan, 2023)
The existence of the Multicultural class is an attraction, because not all schools dare to carry out the Multicultural class program in overcoming social inequalities that often occur. Cultural conflicts and violence in Papua, the assessment of the term dividing individuals through religion, riots, and intolerance are not new discourses that appear in the highlights of the mass media. The multicultural class bridges teaching related to these issues to the nation's children so as not to repeat the same case, realizes the value of Pancasila that we are one, and also interprets the country's motto, namely Bhineka Tunggal Ika. Religion is not necessarily taught to individuals for free, various media and methods are carried out for this teaching collaboration. It is not a taboo subject, Islam teaches the diversity of multicultural education implicitly in the Qur'anic text. So it is not impossible, religion and multicultural education become a harmonious blend in learning. In a society, religion is one of the factors that support life, especially in spiritual life. Therefore, the researcher considers it necessary to do community service based on these social phenomena, with the aim of strengthening the cultivation of religious and social character values for the community by contamination of the existence of various cultures of immigrants who settled with the intention of school students from outside the area.